The magic barrel - Malamud, Bernard; Singer, Isaac Bashevis, 1904-1991.; Bergman, Shelley; April, Arnold; National Jewish Theatre ([Venice, Calif. : L.A. Theatre Works, 1992)
Side one presents a lonely young rabbinic student who seeks out a matchmaker to help him unravel the mysteries of sanity and love. Side two features a writer at a cocktail party forced to become the audience to a New York matron with her own story to tell.
"National Jewish Theatre production"--Narration.
Produced for radio by Chicago Theatres on the Air; adapted and directed by Arnold April.
With special guest Shelley Bergman (side one).
Recorded before a live audience at the Guest Quarters Suite Hotel and broadcast on the radio program Chicago theatres on the air, WFMT, Chicago.
Keywords: Dramas -- Adaptation -- Radio